Survival on the margins: Polish Jewish refugees in the wartime Soviet Union - Adler, Eliyana R. (Harvard University Press, 2020)
Introduction: On the other side -- Esau or Laban? Wrestling with the German and Soviet occupations -- If a man did flee from a lion, and a bear met him: the Soviet embrace -- Jewish luck: deportation to Siberia -- City of want: survival in Central Asia -- Nusekh Poyln or yetsies Poyln? the Polish way or exodus from Poland? -- Conclusion: Expanding the compass of survival.